Características anatômicas de espinheira-santa (Maytenus ilicifolia Mart. ex Reissek e Maytenus aquifolia Mart.) e mata-olho (Sorocea bonplandii (Baill.) Burg. Lanj. & Boer.) para o controle de qualidade da matéria prima - Jacomassi, Ezilda; Machado, Silvia R. [UNESP] (My University, 2003)
Maytenus ilicifolia and Maytenus aquifolia (Celastraceae) both designated espinheira-santa have proven anti-ulcer activity. Morphologic similarities between leaves of espinheira-santa and mata-olho (Sorocea bonplandii), has motivated fakes in the market of phytotherapy. The present work consisted of the anatomical study, including stem and leaf, of the species M. ilicifolia, M. aquifolia and S. bomplandii. Samples of adult leaves and stem of plants located in the cities of Maringá and Marialva were collected. Both are located in the northwest region of Paraná State. The botanical material was prepared with using usual techniques of anatomy. The leaves of both Maytenus species presented great similarities, characterizing itself for the presence of epidermal cells with straight walls, biseriate palisade tissue, petiole vascular system represented by unique amphicribal bundle and sclereids, which were present in the stems of these two species. S. bomplandii leaves differed of Maytenus species for presenting epidermal cells with undulated walls, uniserite palisade tissue, petiole vascular system represented by many collateral bundles and gelatinous fibres. Non-glandular trichomes, glandular trichomes, and laticifer only occur in S. bomplandii.
Anatomical features of the espinheira-santa (Maytenus ilicifolia Mart. ex Reissek and Maytenus aquifolia Mart.) and mata-olho (Sorocea bonplandii (Baill.) Burg. Lanj. & Boer.) for the quality control of the raw material
Keywords: Anatomy; Leaves; Plants medicinal; Stem; botany; Maytenus; Maytenus aquifolia; Maytenus ilicifolia; medicinal plant; nonhuman; phytotherapy; plant; plant leaf; plant stem; quality control; Celastraceae; Sorocea; Sorocea bonplandii